Correlations on the protection of personal data and intellectual property rights in medical research - Popescu, Iulian Gabriel; Sechel, Gabriela; Leaşu, Florin Gabriel; Ţânţu, Marilena Monica; Cotoi, Bogdan Virgil; Rogozea, Liliana Marcela (Romanian journal of morphology and embryology, 2018)
International regulations regarding the protection of individuals concerning the processing of personal data and the free movement of such data highlight the need for their systematization and customization, depending on the purpose for which they are collected and used. Medical legislation is structured so that the constitutional right to healthcare is guaranteed and at the same time be protected by respecting the right to privacy with respect to identity, physiological state of the person and the way this, by health maneuvers, was restored. European Union (EU) legislation is more and more complex related to the patients' right and also to the General Data Protection Regulation (GDPR). After the Second World War, in all Europe the problem related to the human rights become a sensible one in all countries and become aware the importance of clear rules for protecting people, to develop and protect their rights. The article presents the correlation between personal data and intellectual property right in the field of medical research, one of the most dynamic fields of scientific research both in the field of fundamental and applied research. Dissemination of medical information collected through scientific works is subject to the fact that progress in any field should be encouraged, in order to increase the quality of life while, at the same time, creating a balance between the interests of the researcher and the public interest and the interest of the academic community represented by any person in the situation of recourse to a medical service. In the context of the EU guidelines and implementation of GDPR starting to 2018, the medical research and the education of scientific researchers in the field has gone into a new stage of the ethical approach.